Prevalence and root canal morphology of taurodontism analyzed by cone-beam computed tomography in Northern China - Shaorong Li; Ziheng Min; Tianhao Wang; Benxiang Hou; Zheng Su; Chen Zhang (BMC Oral Health)
Abstract Background To evaluate the prevalence and characteristics of taurodontism in northern China by using cone-beam computed tomography (CBCT) and assisting the treatment. Methods The study involved CBCT scans of 8112 teeth from 507 participants of northern China, comprising 217 males and 290 females aged 18 to 60. Analysis was conducted using Shifman and Chanannel’s criteria to assess the prevalence and attributes of taurodontism, examining differences based on tooth position (maxilla and mandible) as well as gender (P < 0.05). Specific morphology including C-shaped canal was recorded. The curvature of the canals was measured using a modified Schneider method. Moreover, we reported two failure cases with taurodontism referred to a retreatment. Results Taurodontism was observed in 113 participants, affecting 23.50% of the males and 21.38% of the females in at least one tooth (P > 0.05). The prevalence was significant higher in maxilla (P < 0.05). The highest incidence of taurodontism was detected in premolars, 9.86% in the maxillary first premolars, and in molars, with 3.94% in the maxillary first molars. Regarding canal curvature, a higher incidence of curved canal could be found in maxillary and mandibular molars of taurodontism (47.50-66.67%), alongside an elevated prevalence of C-shaped taurodontism in mandibular second molars (71.43%). After follow-up, the healing response was satisfactory in both cases. Conclusion The study highlighted a higher incidence of taurodontism in maxilla, indicating a significant association between taurodontism, C-shaped characteristics, and canal curvature. Dentists are advised to carefully consider the presence of special morphologies during taurodontism treatment.